Development of an Agency Partner Portal for RescueMetrics - Arora, Deepkrsna (Wellington Faculty of Engineering Symposium, 2023)
In response to the evolving needs of agency partners and the dynamic digital landscape, this project seeks to transform the user experience within the RescueMetrics web-application by introducing a comprehensive set of new features and pages. The project implemented a new onboarding flow, created an overview one-stop-shop dashboard for aggregated data insights, enabled rebate payment tracking, and implemented account permissions along with brand transfer functionality.